Implementasi Qanun No. 11 Tahun 2018 Tentang Lembaga Keuangan Syariah Pada Koperasi - Makmu, Geubrina (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2023)
Background. Nanggroe Aceh Darussalam provinces is one the provinces that has special autonomy, namely the application of sharia law in all aspects of life, including financial intitutions. Qanun number 11 of 2018 concerning Islamic financial institution in the province of nanggroe Aceh Darussalam as a whole, including sharia financing cooperatives as referred to in article 28 Aim. This research is to show the implementation of qanun no. 11 of 2018 concerning Islamic financial institutions in cooperatives Methods. This research is s type of empirical juridical research with a sociological jurical approach, data collection techniques with interviews and documentation, data analysis is carried out by editing, classification, verification and analysis methods Results.from this study shows that in the implementation of qanun no. 11 of 2018 concerning Islamic financial institutions in cooperatives needs to be improved and reviewed from the mashlahah mursalahthe implementation of this qanun is the need to adapt to the new system but this gives a sense of security to cooperative members